Pengaturan Penggunaan Drone Oleh Masyarakat Sipil Sebagai Upaya Melindungi Keamanan Dan Keselamatan Publik - Suci Nurlaeli; Mubiina, Fathan; Jamaludin, Ahmad (Jurnal Hukum Respublica, 2024)
Drones are a technology that now has the potential to endanger the security and safety of civil society in public spaces, such as disturbing someone's privacy and even causing death. Of course, it is important for Indonesia to create and enforce regulations on the use of drones in public spaces. Therefore, this research was carried out using normative juridical methods to find out the limitations regulated in the use of drones which refer to several Regulations of the Minister of Transportation of the Republic of Indonesia, as well as to find out strategies for preventing security risks from using drones in Indonesia. The results of this research are that there are several restrictions on the use of drones, namely drones must be used during the day, cannot be used in certain areas unless there is permission from the Director General of Transportation, must use VLOS rules, and so on. Apart from that, prevention strategies can be carried out by: drone users must register drones and remote pilots before using drones, supervision by the community and government, outreach and education carried out by the government to the community, and manufacturing drones. The provisions for criminal sanctions for misuse of drones in this law specifically concern government use of drones such as what happened in Florida. It is hoped that these regulations and prevention strategies can minimize the misuse of drones which has the potential to endanger the security and safety of civil society in public spaces.